The role of corporate social responsibility in peacebuilding : a case study of commercial banks in Central division, Kampala Capital Cit y - Lubega, Stevenson (Kampala, 2015)
Unpublished dissertation (MA. PCS) - Makerere University, 2015
Includes bibliographical references (p. 59-66).
Keywords: Peace building -- Uganda -- Kampala Capital City; Banks and banking -- Public relations -- Uganda -- Kampala Capital C ity